The Impact of PDCA Cycle-Driven Nutritional Support on serum Biomarkers and Quality of Life and in Nasopharyngeal Carcinoma Patients Undergoing Radiotherapy: Impact of PDCA Cycle-Driven Nutritional Support on serum Biomarkers - Xiong, Weiming; Mo, Jinying; Weng, Jingjin; Wang, Yongli; Wei, Jiazhang; Ye, Linsong; Li, Min; Qu, Shenhong (Journal of Medical Biochemistry, 2025)
Aim:This study aimed to evaluate the effectiveness of nutritional support guided by the PDCA cycle management model in nasopharyngeal carcinoma (NPC) patients undergoing radiotherapy. Methods:A total of 100 NPC patients were randomly assigned to an observation group (OG) (n = 50) and a control group (CG) (n = 50). The CG received routine nutritional support, while the OG received PDCA cycle-based nutritional support. Key outcomes included blood nutritional biomarkers, quality of life (QoL), incidence of adverse reactions (ARs), and clinical efficacy. Results: Post-treatment analysis revealed that the OG had a significantly higher total effective rate (72%) compared to the CG (38%) (P < 0.05). The OG demonstrated higher albumin, prealbumin, and total protein levels, along with lower CRP levels after treatment. Additionally, significant improvements were observed in cognitive, role, social, physical, and emotional functioning in the OG (P < 0.05). Furthermore, the AR rate was significantly lower in the OG (20%) compared to the CG (36%) (P < 0.05). Conclusion: These findings suggest that PDCA cycle-based nutritional support improves clinical efficacy and QoL, minimizes nutritional risks and ARs, and enhances overall safety in NPC patients undergoing radiotherapy. Serum markers such as serum iron, ferritin, prealbumin, and CRP were effective in monitoring the impact of nutritional interventions on patients’ nutritional and inflammatory status.